The role of transformational leadership in enhancing school culture and teaching performance in Yemeni public schools - Alzoraiki, Mohammed; Ahmad, Abd Rahman; Ateeq, Ali; Milhem, Marwan (Frontiers in Education, 2024)
This study examined the mediating effect of school culture on the relationship between transformational leadership and teaching performance in Yemeni public schools. A stratified random sample of 375 teachers from schools in Sana'a, Yemen, was selected to participate. Data were collected through questionnaires and analyzed using structural equation modelling with SmartPLS 3. The results showed that transformational leadership and a positive school culture significantly predicted better teaching performance. Furthermore, school culture mediated the positive relationship between transformational leadership and teaching performance. These findings provide valuable insights for school leaders on the critical role of school culture in achieving teaching excellence. The results also shed light on mechanisms to improve school culture and educational leadership to implement policies for better student outcomes. Thus, this study addressed a gap in research on the connections between leadership styles, teaching performance, and school culture in the understudied context of Yemen's education system.